LESSON STUDY: THE USING OF PEER TUTORING TOWARD TEFL COURSE OF FOURTH SEMESTER STUDENT AT ENGLISH DEPARTMENT OF COKROAMINOTO PALOPO UNIVERSITY - Rizal, Sjachrun A.M. (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
This research was done to establish our qualities in teaching English as a foreign language. The writers used lesson study method in this research. Data sources that have been used were studentsâ questionnaires, studentsâ interviews, and lecturesâ observation.The data result showed that the students had good positive responses for their academic learning, motivations, social behaviors and attitudes during the learning process by using peer tutoring as a lesson design. Moreover, the lecturerâs observers had good positive responses when they observed the process of learning.Â  The result of this research would be used as a reference that would change our habits in teaching English as foreign language. In the other words, the writers hoped that the teacher and the lecturer aware of their weaknesses in English teaching and they want to be observed by the other teachers and lectures when they teach in the classroom. The writer also hoped that the English student who read this research will get motivation to learn English in various ways. The students should be creative in learning English in order to master the English.